Pelatihan Pembuatan Alat Pendeteksi Gas Elpiji pada Rumah Tangga untuk Siswa SMA se-derajat di Dukuh Kadisoka, Sleman - Listyalina, Latifah (Jurnal Pengabdian Dharma Bakti, 2019)
Government policies in converting energy use from kerosene to LPG have encouraged many people to use LPG gas stoves as fuel for stoves used. Although LPG gas stoves have more practical advantages than using kerosene stoves, they still have disadvantages, namely the danger they cause if there is a gas leak that results in an explosion and causes fires and even casualties. To prevent these fires, it is necessary to detect LPG gas leaks, especially in industries and households. From this, an idea was implemented to provide training in the manufacture of gas leak detection devices. Such is the rationale used in the Training of Making LPG Gas Detection Devices in Households for High School Students in Dukuh Kadisoka, Sleman. Hopefully these activities are beneficial, and can prevent fires caused by LPG gas leakage. This activity was held in June 2018 in Kadisoka hamlet. This activity is expected to be useful in everyday.Keyword:Â detection, Kadisoka, LPG gas leakage